Inferential level of reading comprehension and its relationship with the production of argumentative texts - Leyva Ato, Lady Antuanette (2022)
The purpose of this article was to demonstrate the relationship between the inferential level of reading comprehension and the production of argumentative texts in higher education students. The inferential level of reading comprehension is the reader's ability to understand what is read in order to deduce implicit information from what is explicit. The argumentative textual production implies postulating arguments that support a point of view in a cohesive and coherent way, taking into account the textual structure. The research had a quantitative approach, non-experimental design, with a correlational descriptive level. The probabilistic sample gathered 132 General Studies students from a private Higher Institute (SENATI). The results showed a direct positive correlation using Spearman's Rho r = 0.375 and a p-value 0.001 between the inferential level of reading comprehension and argumentative texts. It was concluded that there is a significant relationship between the inferential level of reading comprehension and the superstructure in the production of argumentative texts.